Efficiency of ectomycorrhizal fungi on phosporus uptake and eucalypt growth promotion - de Souza, Luiz Afonso Borges; Silva Filho, Germano Nunes; de Oliveira, Vetúria Lopes (Pesquisa Agropecuaria Brasileira, 2004)
The potential of ectomycorrhizal fungi to promote plant growth and the mycorrhization control may contribute to important progress towards the exploitation of these fungi commercially. The objective of this work was to evaluate the efficiency of ectomycorrhizal isolates on root colonization, P uptake and growth of Eucalyptus dunnii seedlings under different levels of phosphorus applied. Inocula of the ectomycorrhizal isolates, INRA-Cou (Paxillus involutus), UFSC-Hg93 (Hysterangium gardneri), UFSC-Pt116 (Pisolithus microcarpus) and UFSC-Ch163 (Chondrogaster angustisporus), were aseptically produced in a peat-vermiculite mixture supplemented with liquid culture medium. Plants were grown in a similar substrate supplemented with macro- and micronutrients, under different levels of phosphorus: 0, 0.25, 0.50, 1.00, 2.00, 4.00, and 8.00 mg per plant. The isolates UFSC-Pt116 and UFSC-Ch163 promoted higher root colonization, higher P uptake and plant growth, as determined by plant height and dry matter. Levels of 0.50 and 1.00 mg of P per plant promoted a significant mycorrhizal colonization and an adequate plant growth. The isolates UFSC-Ch163 and UFSC-Pt116 represent a promising alternative for a controlled mycorrhization programme of E. dunnii.